2014
DOI: 10.1007/s12035-014-8917-0
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation During Adolescence Strengthens Retention of Fear Memories and Facilitates Induction of Late-Phase Long-Term Potentiation

Abstract: Social isolation during the vulnerable period of adolescence produces emotional dysregulation that often manifests as abnormal behavior in adulthood. The enduring consequence of isolation might be caused by a weakened ability to forget unpleasant memories. However, it remains unclear whether isolation affects unpleasant memories. To address this, we used a model of associative learning to induce the fear memories and evaluated the influence of isolation mice during adolescence on the subsequent retention of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 77 publications
0
35
1
Order By: Relevance
“…We observed a significant increase in time interacting with the stimulus mouse in neighbor housed mice as compared to group housed mice, suggesting a lower social anxiety phenotype. Few reports have directly investigated effects of social isolation on social and affiliative behaviors, and those that have offer conflicting results [5,[34][35][36][37][38]. Using a similar social interaction task, C57/BL6 males socially isolated since weaning interacted less with an aggressive male conspecific as compared to group housed mice [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed a significant increase in time interacting with the stimulus mouse in neighbor housed mice as compared to group housed mice, suggesting a lower social anxiety phenotype. Few reports have directly investigated effects of social isolation on social and affiliative behaviors, and those that have offer conflicting results [5,[34][35][36][37][38]. Using a similar social interaction task, C57/BL6 males socially isolated since weaning interacted less with an aggressive male conspecific as compared to group housed mice [35].…”
Section: Discussionmentioning
confidence: 99%
“…Few reports have directly investigated effects of social isolation on social and affiliative behaviors, and those that have offer conflicting results [5,[34][35][36][37][38]. Using a similar social interaction task, C57/BL6 males socially isolated since weaning interacted less with an aggressive male conspecific as compared to group housed mice [35]. While we did not observe a difference in social interaction between single and group housed mice, this discrepancy may be explained by the difference in stimulus mice used in our assay since we used a non-aggressive female stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…However, several groups have reported similar behavioral changes in mice that have been socially isolated in adolescence. For example, adolescent social isolation in mice has been shown to lead to increases in anxiety‐like behavior on the elevated‐plus maze (Koike et al ; Kumari et al ; Wei et al , although see Voikar et al ; Zhang et al ), sensory gating deficits (Gan et al ) as well as increased contextual fear and impaired fear extinction (Liu et al ; Pibiri et al ). Other studies have reported increases in home‐cage ethanol intake and preference (Advani et al ; Lopez et al ; Talani et al ), with one of these studies showing that this effect endured for at least 1 month into adulthood (Advani et al ).…”
Section: Modeling Comorbid Ptsd and Aud In Animalsmentioning
confidence: 99%
“…The upregulation of proinflammatory cytokines in the Algamal study [45] is a more predictable and not pathognomonic finding, in the sense that general inflammatory responses across different psychiatric disorders can affect mood, behavior, and cognition [56]. In terms of neuroplasticity, the decrease of hippocampal BDNF levels and the retention of fear memory six months after the RUS paradigm in isolated rats [45] contradicts another study stating that social isolation of rats during adolescence led to hippocampal BDNF increase and retention of fear memories during adulthood [32] and further research is needed to clarify these opposing findings.…”
Section: Discussionmentioning
confidence: 94%
“…Research has found that neonatal isolation stress increased the stable fraction of actin, which is glucocorticoid dependent and these altered actin dynamics at the spines in the juvenile mPFC may explain neocortical dysfunction leading to altered social behavior later in life [31]. Moreover, in another study, the SI of adolescent mice rendered them unable to forget aversive memories when tested one month after the original event and fear memory retention was explained by the increase of brain-derived neurotrophic factor (BDNF) in the hippocampus [32].…”
Section: Introductionmentioning
confidence: 98%